Structural analysis - Hibbeler, Russell C. (Prentice-Hall, 1997)
This book consists of 15 chapters. Chapter 1 provides a brief discussion of the various types of structural forms and loads. The analysis statically determinate structures is covered in the next six chapters. In the second part of the book, the analysis of statically indeterminate structures is covered in five chapters. The third part of the book treats the analysis of structures using matrix methods.